Finite element simulation of bioconvection Falkner–Skan flow of a Maxwell nanofluid fluid along with activation energy over a wedge. (28th August 2020) - Ali, Bagh; Hussain, Sajjad; Nie, Yufeng; Khan, Shahid Ali; Naqvi, Syed Irfan Raza
Abstract: A description of heat transportation in Maxwell nano-fluids mixed with self-motile thermophile microorganisms over a wedged wall is presented in this article. The porous and thermally convective boundary of the wedge undergoes a sudden movement. The physical mechanism is influenced by an invariant magnetic field. A transformed formulation is established in ordinary differential form by involving similarity functions. A robust coding based on finite element analysis is developed in Matlab script. The convergence and accuracy of the solution are tested against reliable criteria. The interest in computational effort centered on the formation of boundary layer patterns for microorganism distribution, fluid temperature, the volume fraction of nano-inclusions, and fluid velocity when influential parameters are varied. The larger Hartmann number Ha, unsteady parameter A, Deborah number β, and wedge parameter m made the flow along the wall faster and produced thinning of the boundary layer. The higher values of Hartmann number, mixed convection, buoyancy ratio parameter, thermophoresis parameter Nt, Brownian motion parameter Nb, wedge parameter m, radiation parameter Rd, and Biot number have raised the fluid temperature. The local heat transfer rate reduces against Nt and it is higher for stretching wedge and smaller for the shrinking wedge. An efficient heat transfer in macro-tech processes may utilize the procedure and findings of this study.